An impedance source modular DC/DC converter for energy storage system: analysis and design. (December 2021) - Bi, Kaitao; Liu, Yue; Zhu, Yixin; Fan, Qigao
Highlights: The proposed converter solves the over- current issue of MMDDC in charge mode. The boost function of impedance source helps to reduce the number of sub-modules. The reduction of sub-modules can reduce the total voltage on energy storage side. The working current on energy storage side is continuous. Shoot through operation can increase the sub-module control degree. Abstract: This paper proposes a novel impedance source modular DC/DC converter for the energy storage system (ESS), which overcomes the drawbacks of traditional modular multilevel DC/DC converter (MMDDC), such as discontinuous current on energy storage side, easy over-current in charge mode, large number of sub-modules etc. A new quasi-Z source (qZS) sub-module is constructed by combining bi-directional quasi Z source and half bridge converter. The bi-directional qZS can make the input voltage of half bridge sub-module controllable, and then solve the over-current issue of the traditional MMDDC in charge mode. Meanwhile, the boosting function of the impedance source can help to reduce the number of sub-modules when the system is applied to the medium and high voltage occasions, simplifying the system structure and improving system efficiency. More importantly, the bi-directional qZS can make the current on energy storage side continuous, improving the lifetime of energy storage device. Detailed analysis about the operation principle and characteristics of the proposed converter are presented in the paper, and the study of control strategy design for the proposed converter is also carried out. At last, the effectiveness of the proposed converter and control strategy is verified by experimental results.